Political polarization in the presidential elections (2018 and 2022): the Northeast and the “others” - Batista, Fabiano Eloy Atílio; Farias , Rita de Cássia Pereira; Teixeira , Débora Pires (Argumentum, 2025)
This research analyses the discourse surrounding Northeastern migration in social media posts on Instagram and Twitter (X-Twitter) during the 2018 and 2022 presidential elections. The study reveals that perceptions of the Northeast are symbolic and shaped by stereotypes that reinforce inequality and prejudice. Employing a qualitative approach, using Content Analysis, the research investigated how these narratives place Northeasterners in a subordinate position and what these stereotypes reveal about the “social question” in Brazil. The results show that the posts often stigmatise the Northeast, blaming the region for socioeconomic problems, and exploit the “social question” as a form of entertainment without addressing its structural causes. These representations reinforce misleading imaginaries and strengthen exclusionary discourse and historical violence.
Keywords: Migration; Politics; Social Networks; Brazil